The Development, Validation, and Application of a UHPLC-HESI-MS Method for the Determination of 17 Cannabinoids in Cannabis sativa L. var. sativa Plant Material - Joanna Kanabus; Marcin Bryła; Marek Roszko (Molecules, 2023)
Cannabinoids are an important group of secondary metabolites found in the plant Cannabis sativa L. The growing interest in the use of hemp in food production (e.g., hemp teas, hemp cookies) makes it necessary to develop a method for determining these compounds in the plant, both fresh and dried. The selection of a suitable extraction liquid for the extraction of cannabinoids and the development of a method for the determination of 17 cannabinoids is a prelude to the development of an effective method for the extraction of these compounds. In the present study, a novel, simple, and efficient method was developed and validated for the determination of up to 17 cannabinoids in fresh plant parts (inflorescences and leaves) of Cannabis sativa L. and in dried material, including hemp teas. Analyses were performed using ultra-high-performance liquid chromatography-Q-Exactive Orbitrap mass spectrometry setup operating with a heated electrospray interface (UHPLC-HESI-MS). Based on the comparison, methanol was selected as the best for the extraction of cannabinoids from fresh and dried material. The efficiency and validity of the method were assessed using certified reference material (dried Cannabis) and confirmed by z-score from participation in an international proficiency test conducted by ASTM International for dried hemp.